CZECH-GERMAN RELATIONS IN THE MIDDLE OF THE 9th – THE FIRST THIRD OF THE 10th CENTURY (Південний архів (історичні науки), 2024)
The purpose of the scientific study is to reveal the peculiarities of relations of Czech princes with the rulers of the East Frankish, and hence the German kingdom, in the period from the middle of the 9th to the 30s of the 10th century. Principles of historicism, objectivity and scientific reliability are the methodological basis of the work. Historical-systemic and analytical methods were used. The scientific novelty consists in the comprehensive study of the outlined problem in the context of the international situation in Central Europe and the process of state formation of Slavic tribal unions that settled on the territory of today’s Czechia. Conclusions. At the beginning, relations of the Czech princes with the East Frankish (German) kingdom had a predominantly military character. In the middle of the IX century the East Frankish King Louis II of Germany organized several armed campaigns against Czech princes. Soon the Czech lands fell under the suzerainty of Sviatopolk, the ruler of the Great Moravian State. But after his death the Czech princes, trying to free themselves from the power of Great Moravia, surrendered directly to the East Frankish king Arnulf, the nucleus of whose possessions was the Duchy of Bavaria. With the election of the Saxon Duke Henry I Ptakholov to the German throne there was strengthening of the royal power. The new ruler invaded the Czech lands and reached Prague. Czech Prince Vaclav I Prshemyslovych intended to defend the country, but the advantage was on the side of the assailants. So Vaclav I had to submit to the fate and agreed to the pay the contribution and possibly also to fulfill some other fiefs obligations. As a result, during his reign, the Czech principality of Prshemyslovych found itself in the sphere of influence of Saxony, and therefore, in a vassal state dependence on the German kingdom.
Keywords: Czech state, Prshemyslovychy Borzhivoj, Vaclav, Great Moravia, St. Methodius, Sviatopolk, East Frankish Kingdom, Louis II of Germany, Arnulf, Henry I Ptakholov.